PERAN SERTA MASYARAKAT DALAM PENGELOLAAN RUANG TERBUKA HIJAU (RTH) DI KOTA BANDUNG - Astriani, Nadia (Faculty of Law, Parahyangan Chatolic University, 2015)
As a vehicle for social interaction, open spaces are expected to be able to link all of members of society (or the local community) without differentiating between their social, economic and cultural background. Green open space forms part of the urban space available in a region that has been filled with plants in order to bring ecological, social, cultural and aesthetic benefits. From the research conducted previously, it may be gathered that reaching the green open space proportion of 30% in the city region could only have been accomplished by involving many stakesholders, especially the local community members. This phenomenon piqued the interest of the researchers to conduct further research into the active participation of society (local community members) in the management of green open space and into the policies issued by the government to increase this effort. The outcome shows that the active participation of the local community members in the utilization of green open space serves not only to supervise the government policies, but it also plays an important role in managing and maintaining the green open space in their neighborhood. The expansion of the local communityâs grasp of the concept being not only the party affected by its impact, but also as the interest and pressure group broadening its active participation by participating in managing the green open space, and even expanding the green open space by making agreements with the government. On the other hand, the government itself has been making various efforts to increase the active participation from society by encouraging the usage of Corporate Social Responsibility to manage the green open space and offer training sessions and courses to the local community involved.